FLIGHT ACTIVITY OF THE JATAÍ BEE (TETRAGONISCA ANGUSTULA) IN ANÁPOLIS, GOIÁS (CIPEEX, 2025)
Meliponiculture is a form of stingless bee farming for honey production, pollination, and environmental maintenance. Meliponiculture presents itself as a viable alternative for sustainability and environmental protection, as pollination is essential for most flowers to produce fruit, which then serves as food. This study provides information on the flight behavior of Tetragonisca angustula bees in Anápolis between May and August 2024. The study was conducted at UniEvangelica, where a hive from the institution's existing meliponary was selected. Every day, with the aid of a Wi-Fi surveillance camera, information on the time and temperature at the beginning and end of the bees' flight activity was recorded.The results show that there is consistency in flight activity times; however, atypical temperature conditions can delay the start of jataí bee activities by up to four hours. This factor did not interfere with the end of daily flight activities.
Keywords: Stingless bee; Climate; Honey; Temperature